Crecimiento en altura y diámetro de plántulas de Iryanthera tessmannii Mgf. en vivero con aplicación de sustratos orgánicos. Puerto Almendra, Loreto, Perú - 2021 - Cardenas López, Cristopher Paul (2022)
The trial was carried out in the CIEFOR - Puerto Almendra - FCF - UNAP nursery, San Juan Bautista district, Maynas province, Loreto region. The objective was to evaluate the growth in height and diameter; survival and quality of naturally regenerating seedling of Iryanthera tessmannii Mgt. in nursery in different organic substrates. 15 plots of 2.0 m x 0.3 m each were used; the experimental design was simple at random, with control, 4 treatments and 3 repetitions. The description was, witness t0 = 100% natural land; treatments: t1 = 50% natural soil + 50% decomposed sawdust; t2 = 40% natural soil + 60% decomposed sawdust; t3 = 30% natural earth + 60% decomposed sawdust + 10% sand, t4 = 20% natural earth + 70% decomposed sawdust + 10% sand. The results indicate that t4 presented the greatest increase in height with 4,5 cm and the greatest increase in diameter was in t3 with 0.9 mm; the maximum survival of the evaluated seedlings was recorded in t3 and t4 with 70% of live seedlings; seedling quality was good in t4 and was generally poor.